The effect of tempe biscuit consumption on increasing anemia youth Hb levels - Siti Patimah; Meti Megawati (Syntax Idea, 2022)
Anemia occurs a lot in the community, especially in adolescents and pregnant women.Ministry of Health research on anemia prevalence in Indonesia is 21.7% with anemia sufferers aged 5-14 years 26.4% and 18.4% aged 15-24 years (Ministry of Health, 2014). Young women have ten times greater risk of anemia compared to young men. The most common cause of anemia is iron deficiency which includes 50% of all cases of anemia. One obstacle in giving TTD tablets to adolescents is that they are not consumed by teenagers for various reasons. One of the alternative efforts to treat anemia is Fe fortification. The research method used in this study is a type of experimental research. The research design used at the clinical trial stage was True Experimental and the product testing phase was quasi-experimental, with the design of the Two Group Pretest Posttest Design. The population in this study were students of the seventh grade of Tasikmalaya Middle School 9 with 178 people. Based on the calculation of the sample obtained a sample size of 43 people. The sampling technique uses purposive sampling technique. The results were analyzed using univariate and bivariate analysis with analysis of non parametric Wilcoxon test. The results of the study found that the organoleptic sample E test had a higher value than the other samples so that sample E was selected. The statistical test results of the treatment group pretest mean is 10.22 and the posttest mean is 10.35. For the median pretest 10.35 while the median posttest was 10.60. There was a significant increase from the results of the posttest pretest. Bivariate testing with the Wilcoxon test obtained a value of Ï 0,000 <0,05 so that it can be concluded that there was an effect of iron fortification and vitamin C on tempe biscuits on the levels of juvenile Hb anemia.